Updates on Erdheim-Chester disease - Ismail Elbaz Younes; Austin Ellis; Xiaohui Zhang (Elsevier, 2022)
Erdheim-Chester disease (ECD) is a non-Langerhans cell histiocytosis characterized by multisystemic proliferation of histiocytes in a background of fibrosis and inflammation. Patients with ECD have diverse clinical manifestations with multiple organ or system involvement, and pathognomonic radiographical findings such as symmetric cortical osteosclerosis of the diaphysis and metaphysis of the long bones in the lower extremities, "coated aorta", and "hairy kidney". Histopathologically, lesions are composed of epithelioid/foamy histiocytes with fibrosis and admixed inflammatory cells. Most cases of ECD harbor an activating mutation in the MAPK pathway, most commonly BRAF V600E mutation. Prognosis has improved with the use of multiple treatment modalities and the advent of novel targeted therapies.